The perception of genetic diseases and premarital screening tests in the central region of Saudi Arabia - Mariam M. Al Eissa; Fahad Almsned; Reem R. Alkharji; Yousif M. Aldossary; Raghad AlQurashi; Esraa A. Hawsa; Sahar M. AlDosari; Amerh S. Alqahtani; Raniah S. Alotibi; Raed Farzan; Reema Alduaiji; Suha M. Sulimani; et al. (BMC, 2024)
Abstract The prevalence of consanguineous marriages (CMs) varies worldwide from one country to another. However, the Middle East stands out as a region with a notably high rate of CMs. CM is particularly widespread in Saudi Arabia, where the prevalence of autosomal recessive genetic diseases has increased. This study aims to identify the Saudi population's awareness of genetic diseases and premarital screening tests (PMSTs). It also seeks to understand couples' perceptions of genetic diseases before and after marriage and their attitudes towards PMSTs and genetic counselling (GC) in reducing the risk of CM. Through the administration of online questionnaires, this cross-sectional study surveyed 2,057 participants to assess their awareness of genetic diseases and their understanding of testing and preventive measures for inherited diseases. Descriptive analysis, nonparametric chi-square tests and logistic regressions were performed to assess the association of categorical responses. This study included 2,035 Saudi Arabian respondents. A significant correlation was found between positive family history and partner selection (p = 0.001), as well as between partnering within the same tribe (p = 0.000139), with a different tribe (p = 0.000138) and from another family (p = 0.000489). About 91.3% of participants expressed agreement regarding the need to enhance public awareness and knowledge concerning genetic disorders, while 87% agreed that increased government regulations are required to prevent the spread of genetic diseases in affected families. Despite increased awareness of genetic diseases and PMSTs, there appears to be a lack of understanding regarding the limitations of PMSTs. The persistently high rate of CM underscores the challenge of altering marriage customs. Further governmental efforts are required to promote awareness of alternative reproductive options, establish new regulations and expand screening programmes.